Icelandic pelagic fishing vessels_Production_Exports_CatchValues_2005-2018 - Viðarsson, Jónas R. (Zenodo, 2019)
Number of ships in Iceland, gross tonnage (GT), power (kW) and home ports. Pelagic catches by species, landing value, export value, production etc. : Data used as background for development of climate adaptation plans in the ClimeFish project